Sonic Hedgehog Signaling in Cerebellar Development and Cancer - Wang, Wanchen; Shiraishi, Ryo; Kawauchi, Daisuke (Frontiers in Cell and Developmental Biology, 2022)
The sonic hedgehog (SHH) pathway regulates the development of the central nervous system in vertebrates. Aberrant regulation of SHH signalling pathways often causes neurodevelopmental diseases and brain tumours. In the cerebellum, SHH secreted by Purkinje cells is a potent mitogen for granule cell progenitors, which are the most abundant cell type in the mature brain. While a reduction in SHH signalling induces cerebellar structural abnormalities, such as hypoplasia in various genetic disorders, constitutive activation of SHH signalling often induces medulloblastoma (MB), one of the most common pediatric malignant brain tumours. Based on the existing literature on canonical and non-canonical SHH signalling pathways, emerging basic and clinical studies are exploring novel therapeutic approaches for MBs by targeting SHH signalling at distinct molecular levels. In this review, we discuss the current consensus on SHH signalling mechanisms, their roles in cerebellar development and tumourigenesis, and the recent advances in clinical trials for MBs.